DETERMINING THE KEY PERFORMANCE INDICATORS FOR MANAGING THE WAREHOUSE PERFORMANCE: A CASE STUDY OF INTERNATIONAL LOGISTIC COMPANY - Chakma, Aornob (My University, 2024)
Measuring the performance of a warehouse is necessary to enhance the efficiency of the logistics system. To enhance warehouse efficiency, it is essential to define Key Efficiency Indicators (KPIs). This study attempts to discover the KPIs of warehouses to enable warehouse managers to take corrective measures quickly and effectively for their warehouses. This master's thesis is based on a case study that was conducted at DHL, which is a multinational corporation. A qualitative methodology was used in this study, and primary data was gathered via a total of ten interviews, both formal and semi-structured. KPIs and operation and process management were the subjects of secondary data analysis, which included perusing scholarly articles. In addition, internal papers were used as a supplementary source. This study has found 13 KPIs that are associated with warehouse operations. It has been determined that productivity and demand forecast accuracy are the two most important key performance metrics. This research will add to the knowledge about suitable KPIs used for measuring warehouse performance. KEYWORDS:
Keywords: logistics; supply chains; measurement; warehousing; performance management; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business